Complementarities between Labour Market Institutions and Their Causal Impact on Youth Labour Market Outcomes - Niall O'Higgins; Giovanni Pica (Institute of Labor Economics (IZA), 2019)
We analyse theoretically and empirically the effects on young people's labour market outcomes of two specific labour market institutions and their interaction: employment protection legislation andactive labour market policy. The paper examines recent policy reforms in Italy focusing on the impact of the 2012 Fornero reforms of employment protection legislation as well as the initial impact of the EU-wide Youth Guarantee scheme introduced in Italy in March 2014. The paper then examines how these two policy reforms interacted. The analysis first confirms the finding that the Fornero reform increased permanent hires particularly amongst the very youngest workers; it then goes on to find that the YG was indeed successful in increasing the hires of young people, although this operated through a statistically significant increase in female hires on temporary contracts. Third, it finds some evidence of dampening effect of the YG on EPL reforms as predicted by theory.
Keywords: J13; J63; J68; 330; youth employment; job search; ALMPs; EPL